DESIGN, AND MANUFACTURING A SMALL-SCALE WIND TUNNEL FOR HEAT TRANSFER ANALYSIS OF FLAT PLATE AND FINNED PLATE HEAT SINKS - SAEED, ARKAN F.; ABBO, ODAY A. (Journal of Duhok University, 2021)
Application that utilize heat sinks for cooling electrical devices have been increased significantly during the last decade. In present work, the design and installation of small-scale wind tunnel have been executed. An experimental analysis of flow over a flat plat combined with constant heat flux have been investigated to ensure the effectiveness of the device. The design satisfied the basic equations of fluid flow to get the required laminar flow before the test section. The calculations depend on the change in heat flux across the flat plate and obtained results are compared with the previous published results for validation. Experimental analysis of constant heat flux from a horizontal rectangular fin array (HRFA) under controlled forced convection heat loss. The characteristics are investigated for fin with L / H = 1.416; the effect of various parameters such as heater input with different fluid flow velocity on average heat transfer coefficient (h) have been studied. The dimensionless number analysis like Nusselt number (Nu), Reynolds number (Re), were investigated. The heat transfer from surface may, generally, be enhanced by increasing the coefficient of heat transfer between a surface and its surrounding, or by increasing the area of heat transfer surface. An empirical correlations have been differentiated relating Nusselt and Reynolds numbers for both flat plate heat sink with the range 9.3x103  Re  19.1x103 , and Pr < 1.0 with a total error 5%, and finned plate heat sink with the range 7x103  Re  22.5x103 , and Pr < 1.0 with a total error 6.4%.